Investigation of Al2O3 induced variations in the structural parameters in strontium borosilicate glasses using solid state NMR - Illath, Kavya; Ojha, Prasanta K.; Rath, Sangram K.; Ajithkumar, T. G. (Physical Chemistry Chemical Physics, 2023)
The physical properties of oxide glasses are crucially dependent on the atomistic structural speciation. In this study, we investigate the variation in the local ordering in the glass network of strontium borosilicate glasses (34.82 SrO, 51.84 B2O3, 13.34 SiO2 in mol%) with a progressive substitution of B2O3 by Al2O3 and estimate the structural parameters: the oxygen packing fraction, and the average network coordination number. The coordination of the network forming cations at various glass compositions is determined using B-11, Al-27, and Si-29 solid-state nuclear magnetic resonance (SSNMR). The SSNMR reveals that at the higher substitution of B2O3 by Al2O3 in the glass composition, the coordination network of Al3+ exists predominantly in the 4 coordinated state, the network forming B3+ cations transform from a tetrahedral BO4 to a trigonal BO3 structure, and the Q(4) form of silicates is dominant. The average coordination number and the oxygen packing fraction were calculated using the parameters obtained from the SSNMR results, and it is observed that the average coordination number decreases, and the oxygen packing fraction increases on incorporating Al. It is interesting to note that some of the thermophysical properties of these compositions closely follow the pattern shown by the average coordination number and the oxygen packing fraction.